Both exogenous 5-HT and endogenous 5-HT, released by fluoxetine, enhance distension evoked propulsion in guinea-pig ileum in vitro - Gwynne, Rachel M.; Clarke, Amanda J.; Furness, John B.; Bornstein, Joel C. (Frontiers in Neuroscience, 2014)
The roles of 5-HT3 and 5-HT4 receptors in the modulation of intestinal propulsion by luminal application of 5-HT and augmentation of endogenous 5-HT effects were studied in segments of guinea-pig ileum in vitro. Persistent propulsive contractions evoked by saline distension were examined using a modified Trendelenburg method. When 5-HT (30 nM), fluoxetine (selective serotonin reuptake inhibitor; 1 nM), 2-methyl-5-HT (5-HT3 receptor agonist; 1 mM), or RS 67506 (5-HT4 receptor agonist, 1 μM) was infused into the lumen, the pressure needed to initiate persistent propulsive activity fell significantly. A specific 5-HT4 receptor antagonist, SB 207266 (10 nM in lumen), abolished the effects of 5-HT, fluoxetine, and RS 67506, but not those of 2-methyl-5-HT. Granisetron (5-HT3 receptor antagonist; 1 μM in lumen) abolished the effect of 5-HT, fluoxetine, RS 67506, and 2-methyl-5-HT. The NK3 receptor antagonist SR 142801 (100 nM in lumen) blocked the effects of 5-HT, fluoxetine, and 2-methyl-5-HT. SB 207266, granisetron, and SR 142801 had no effect by themselves. Higher concentrations of fluoxetine (100 and 300 nM) and RS 67506 (3 and 10 μM) had no effect on the distension threshold for propulsive contractions. These results indicate that luminal application of exogenous 5-HT, or increased release of endogenous mucosal 5-HT above basal levels, acts to lower the threshold for propulsive contractions in the guinea-pig ileum via activation of 5-HT3 and 5-HT4 receptors and the release of tachykinins. The results further indicate that basal release of 5-HT is insufficient to alter the threshold for propulsive motor activity.